Skill Mix Management in Nursing Services; A Mini Project in A Public Hospital in Jakarta - Yuni Azizah; Rr. Tutik Sri Hariyati; Tuti Afriani; Nurdiana Nurdiana; Wahyu Kusumadi Retnoningtyas (GLOBAL HEALTH SCIENCE GROUP, 2025)
Skill mix includes the nurse workforce size, education level, and clinical experience, nursing hours per patient day, the ratio of nurses to patients (qualified and unqualified), and the various skills and training required to fulfil patient care needs. The aim of this study was to optimally manage the skill mix management system in nursing by allocating various skills and roles within the nursing team to provide safe, effective, and efficient care. This study used a mini-project and analysed the results and implementation gaps through a literature review. Problems were assessed using fishbone diagrams, with alternative solutions developed in a Plan of Action (POA) framework consisting of implementation, Evaluation, and Follow-up phases. Participants were nursing staff, consisting of 2 head nurses and 63 nurses (Primary Nurses and Associate Nurse). The implementation of this study began with the preparation and workshop of technical guidelines on skill mix management in nursing. Data were collected through interviews, questionnaires, field observations, and document reviews conducted from April 22 to May 16, 2024, involving nursing managers and staff on the 3rd and 6th floors of Inpatient Building A. The data were then analyzed descriptively using the nursing management function framework, which includes planning, organizing, staffing, directing, and controlling.Evaluation, through observation and interviews, showed that 80% of the technical guidelines were well structured. There was a focus on care planning patterns, patient delegation models, and preparation of service schedules. Effective nursing skill mix management requires risk mitigation strategies, such as the FMEA approach, as well as close supervision and improved staff competence